2018
DOI: 10.1051/matecconf/201818202020
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of vibro-acoustic impact of chainsaws with electric and combustion drives

Abstract: Chainsaws generate high level vibrations and noise during work. No matter what type of the drive (electric, combustion) they exceed the per-missible levels defined for a standard eight-hour working day. The intensity of a vibro-acoustic impact on chainsaw operators depends on many factors. One of them is the type of the drive. This is due to significant differences in saw design (inter alia characteristics of the drive, rotational speeds - quasi-constant for an electric drive and variable for a combustion one)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The analyses indeed highlight significant exceeding of the thresholds set by law in terms of both noise and gaseous emissions. Prolonged exposure to these physical and chemical agents [14] is the main cause of various occupational diseases.…”
Section: Health Implicationsmentioning
confidence: 99%
“…The analyses indeed highlight significant exceeding of the thresholds set by law in terms of both noise and gaseous emissions. Prolonged exposure to these physical and chemical agents [14] is the main cause of various occupational diseases.…”
Section: Health Implicationsmentioning
confidence: 99%
“…A study done by Rukat et al 23 showed that the impact of vibration and noise emitted from a chainsaw depends on several factors including the type of the drive (electric vs combustion); even with same or similar power, chainsaw with different type of drive may generates noise and vibrations with different magnitude. Chainsaw with combustion engine showed a higher sound level pressure compared to electric chainsaw.…”
Section: Sound Intensitymentioning
confidence: 99%
“…Kristinsdóttir and D. Corredor in 2011 showed that electric chainsaws using batteries have a lower overall environmental impact than those powered by petrol [24]. On the other hand, vibration and noise emission tests carried out in 2018 by the research group led by W. Rukat proved that -regardless of the power unit type (electric, combustion) -noise and vibration emissions levels determined for a standard eight-hour working time are exceeded [25]. In the same year, comparative tests of petrol and electric (battery) saws were carried out in real working conditions while cutting trees.…”
Section: Klasycznementioning
confidence: 99%